Switching between formations for multiple mobile robots via synchronous controller - Sanhoury, Ibrahim M. H. (IEEE, 2012)
This paper proposes a new synchronous control law to perform multiple mobile robots trajectory tracking while maintaining time-varying formations. Each robot is controlled to track its desired trajectory while synchronizing its motion with the two nearby robots to maintain the desired time-varying formation. The dynamic model of the wheeled mobile robot (WMR) is derived, so as, it can be divided into a translational and rotational model, in order to control each model separately. Then, a synchronous controller for each robot's translation is proposed to guarantee the asymptotic stability of both position and synchronization errors. Also, an orientation controller is proposed to ensure that the robot is always oriented towards its desired position. The simulation results verify the effectiveness of the proposed synchronous controller in the formation control tasks.